Serum albumin and total protein level as plausible marker for diagnosis of protein energy malnutrition in children under age 5 years - Gupta, Saroj Sanjeev; Gupta, Pranav Sanjeev (International Journal of Contemporary Pediatrics, 2020)
Background: The circulating concentration of transport protein, traditionally albumin, has been used to define protein deficiency. However, few studies have been conducted to see if there is any correlation between serum total protein and albumin levels in children with PEM. Hence the study was planned to estimate serum total protein, serum albumin levels in children with PEM and healthy controls. Methods: All the children were divided in two groups. Case Group A consist of 250 children with protein energy malnutrition and control Group B consist of healthy 250 children. Venous blood of amount 3 ml was collected with full aseptic precautions. The blood was collected in the EDTA vacutainer and test tube. Serum total protein was estimated by Biuret method, serum albumin was estimated by Bromocresol green dye method (BCG dye). Results: When the mean serum levels of albumin levels and the total protein levels were measured in the controls as well as case groups, there was decrease in levels in case group as compared to control group. This difference of decrease when evaluated statistically it was found to be statistically significant. When the albumin/globulin ratio was calculated in both the groups, it was found to be statistically lower in case group as compared to control group. PEM children have low serum total protein and albumin levels as compared to healthy controls (p<0.001), this is probably due to decreased intake of proteins and reduced biosynthesis. PEM children have lower hemoglobin levels as compared to healthy controls; this is probably due to deficiency of iron and other micronutrients, which is often found in a child with malnutrition. Conclusions: Early diagnosis and prompt management of PEM and its complications can prevent development of permanent physical and mental retardation.